Dicephalic Parapagus Conjoined Twins in a 37 Week Dichorionic Twin Pregnancy: A Case Report - Febriani Febriani; Didik Suhendro; Nisa Faradisa Hernita (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Introduction: Conjoined twins are a rare congenital anomaly resulting from incomplete embryonic division between days 13 and 15 post-fertilization. Dicephalic parapagus is exceptionally rare, characterized by two heads on a single trunk with variable degrees of organ sharing, and is associated with high perinatal morbidity and mortality.Case presentation: A 20-year-old gravida 3 para 2 woman at 37 weeks was referred with suspected conjoined twins. Ultrasound revealed key clinical findings consistent with dicephalic parapagus, including two heads, a single thorax containing one heart, and shared abdominal organs (one liver, one kidney, one urinary bladder, and two gallbladders). After multidisciplinary planning, an elective cesarean section was performed, delivering live conjoined twins with ambiguous genitalia. The neonates were admitted to the NICU for stabilization and further imaging. The mother had an uncomplicated postoperative recovery and remained hemodynamically stable. The primary diagnosis was dicephalic parapagus with shared vital thoracoabdominal structures. The presence of a single functional heart, identified prenatally and confirmed postnatally, is the most decisive prognostic factor and significantly limits the possibility of surgical separation. This case highlights the importance of early prenatal detection and the role of coordinated multidisciplinary management.Conclusions: As a rare and complex case, this report underscores the challenges of late diagnosis of severe congenital anomalies in resource-limited settings. It emphasizes the need for improved antenatal screening, comprehensive parental counseling, and ethical considerations when managing conjoined twins with non-separable anatomy.Kembar Siam Parapagus Dicephalus pada Kehamilan Kembar Dikorionik 37 Minggu: Laporan KasusAbstrakPendahuluan: Kembar siam merupakan anomali kongenital yang sangat jarang terjadi akibat kegagalan pembelahan diskus embrionik antara hari ke-13 hingga ke-15 pascafertilisasi. Parapagus disefalus merupakan kasus yang sangat langka, ditandai dengan dua kepala pada satu batang tubuh dengan derajat berbagi organ yang bervariasi, serta memiliki morbiditas dan mortalitas perinatal yang tinggi.Presentasi kasus: Seorang wanita berusia 20 tahun dengan gravida 3 para 2 pada usia kehamilan 37 minggu dirujuk dengan dugaan kehamilan kembar siam. Pemeriksaan ultrasonografi menunjukkan temuan klinis penting berupa parapagus disefalus, dengan dua kepala, satu toraks berisi satu jantung, serta organ abdomen yang berbagi, termasuk satu hati, dua kantong empedu, satu ginjal, dan satu kandung kemih. Setelah perencanaan multidisiplin, dilakukan seksio sesarea elektif dan berhasil melahirkan bayi kembar siam hidup dengan genitalia ambigu. Keduanya dirawat di NICU untuk stabilisasi dan pemeriksaan lanjutan, sementara ibu menjalani pemulihan pascaoperasi tanpa komplikasi. Diagnosis utama adalah parapagus disefalus dengan berbagai organ vital torakoabdominal yang digunakan bersama. Keberadaan satu jantung fungsional merupakan faktor prognostik paling kritis yang sangat membatasi kemungkinan dilakukan pemisahan bedah. Kasus ini menekankan pentingnya deteksi prenatal dini, konseling orang tua yang komprehensif, dan tata laksana perinatal yang terkoordinasi.Kesimpulan: Sebagai kasus yang sangat langka dan kompleks, laporan ini menunjukkan tantangan diagnosis terlambat pada anomali kongenital berat, terutama di fasilitas kesehatan dengan sumber daya terbatas. Kasus ini menegaskan perlunya peningkatan kualitas skrining antenatal, edukasi keluarga, serta pertimbangan etis dalam menangani kembar siam dengan anatomi yang tidak dapat dipisahkan.